FROM LOCAL HEALING TO GLOBAL READABILITY: EWTC AND MULTI STAKE HOLDER COLLABORATION FOR EMERGING WELLNESS TOURISM DESTINATIONS - Dahlia Husain; Nirwanto Ma'ruf; Ana Mariana; Yumanraya Noho (English Review: Journal of English Education, 2026)
This study examines how English for Wellness Tourism Communication (EWTC) and multi-stakeholder collaboration contribute to transforming Gorontalo’s local healing practices into globally readable wellness tourism narratives. Positioned within the growing discourse on wellness tourism and English for Specific Purposes (ESP), the research addresses a critical gap in communication competence among emerging destinations seeking international visibility. Using a sequential explanatory qualitative design, data were collected through semi-structured interviews and focus group discussions involving government representatives, tourism businesses, community-based providers, and an expert validation panel. Thematic analysis identified recurring communication barriers, including limited wellness-specific vocabulary, weak cultural storytelling, inconsistent digital messaging, and low English-speaking confidence. Based on these findings, the study developed and validated a structured EWTC competency framework covering genre chains across the tourist journey, ethical messaging, intercultural explanation strategies, and digital promotion skills. The results demonstrate that improved clarity, cultural interpretability, transparency, and coordinated stakeholder messaging significantly strengthen destination image formation and global trust. The study contributes theoretically by positioning wellness tourism as a specialized ESP domain and practically by offering a context-sensitive communication model for community-based destinations. These findings highlight that global readability is not merely linguistic simplicity but a multidimensional construct linking language, ethics, culture, and collaboration in sustainable wellness tourism development.